Clinical and epidemiological characteristics and morphological peculiarities of urogenital trichomoniasis nowadays - H. I. Mavrov; T. V. Osinska; P. V. Fedorych (Zaporozhye State Medical University, 2020)
Importance of the topic is stipulated with the current significant spread of infectious diseases of the urogenital tract, caused by the representatives of the protozoa genus Trichomonas. Aim. Evaluate the prevalence and peculiarities of contemporary trichomonas infection (Trichomonas vaginalis, Pentatrichomonas hominis, Trichomonas tenax), with the consideration of the associated bacterial infections that cause the urogenital pathology and the ultrastructural peculiarities of Trichomonas vaginalis morphotypes in the patients with chronic infectious diseases of the genitourinary organs. Material and methods. The research was carried out among 377 patients with chronic infectious diseases of the genitourinary organs. Routine bacterioscopic and bacteriological methods were applied. In addition, Trichomonas tenax and Pentatrichomonas hominis were detected using real-time polymerase chain reaction and applying original experimental primers. The ultrastructure of the trichomonads was studied using a PEM-125K electron microscope equipped with the SAI-01A (SELMI) system, using a CCD camera DX 2 and KAPPA software package. Results. Trichomonas vaginalis was detected in 48.3 % using the methods of optical microscopy and culture media inoculation. Trichomonas tenax was detected in 18.2 % and Pentatrichomonas hominis was detected in 67.1 % with the polymerase chain reaction. Development of the pathological process in the urogenital system of the studied patients (up to 90 %) was caused with the microbial associations, in particular, with Ureaplasma urealyticum (26.1 %), Chlamydia trachomatis (16.7 %), Mycoplasma hominis and Mycoplasma genitalium (13.9 %) and various kinds of opportunistic pathogenic microflora (up to 60 %), which lead to dysbiosis of urogenital system. It was proved that the oval morphotype Trichomonas vaginalis may be referred to the virulent forms; it was detected more often (68 %) than the piriform morphotype. Conclusions. Possible presence of trichomonads of three species: Trichomonas vaginalis, Trichomonas tenax, Pentatrichomonas hominis, in particular in pathological microbial associations, as important factors of the emergence and / or development of the pathological process, was established in the human genitourinary system. It is reasonable to refer the oval morphotype Trichomonas vaginalis to the virulent forms of this agent.